QD/2D Hybrid Nanoscrolls: A New Class of Materials for High‐Performance Polarized Photodetection and Ultralow Threshold Laser Action. Issue 45 (20th October 2020) - Ghosh, Rapti; Lin, Hung‐I; Chen, Yu‐Siang; Singh, Mukesh; Yen, Zhi‐Long; Chiu, Shengkuei; Lin, Hsia‐Yu; Bera, Krishna P.; Liao, Yu‐Ming; Hofmann, Mario; Hsieh, Ya‐Ping; Chen, Yang‐Fang
Abstract: Nanoscrolls are a class of nanostructures where atomic layers of 2D materials are stacked consecutively in a coaxial manner to form a 1D spiral topography. Self‐assembly of chemical vapor deposition grown 2D WS2 monolayer into quasi‐1D van der Waals scroll structure instigates a plethora of unique physiochemical properties significantly different from its 2D counterparts. The physical properties of such nanoscrolls can be greatly manipulated upon hybridizing them with high‐quantum‐yield colloidal quantum dots, forming 0D/2D structures. The efficient dissociation of excitons at the heterojunctions of QD/2D hybridized nanoscrolls exhibits a 3000‐fold increased photosensitivity compared to the pristine 2D‐material‐based nanoscroll. The synergistic effects of confined geometry and efficient QD scatterers produce a nanocavity with multiple feedback loops, resulting in coherent lasing action with an unprecedentedly low lasing threshold. Predominant localization of the excitons along the circumference of this helical scroll results in a 12‐fold brighter emission for the parallel‐polarized transition compared to the perpendicular one, as confirmed by finite‐difference time‐domain simulation. The versatility of hybridized nanoscrolls and their unique properties opens up a powerful route for not‐yet‐realized devices toward practical applications. Abstract : The spirally wrapped 2D material scroll structure after getting hybridized with semiconductor quantum dots achieves lasing action with a remarkably low lasing threshold (≈0.008 kW cm −2 ) along with a 3000‐fold enhanced photodetection because of the efficient light trapping inside the nanoscroll. This helical nanostructure is even capable of sensing 12‐fold enhanced parallel‐polarized luminescence compared to the perpendicular direction.